HIV‐1/2 screening in blood centers: implementing a two‐step serological screening assay approach to reduce donor deferral. Issue 6 (20th March 2019) - Stoyanov, Evgeniy; Gozlan, Yael; Wax, Marina; Levin, Evelina; Shvartz, Lea; Shinar, Eilat; Mendelson, Ella; Mor, Orna
Abstract : BACKGROUND: Screening blood donations for human immunodeficiency virus 1/2 (HIV‐1/2) infection in blood centers is often done with a highly sensitive 3rd‐generation immunoassay which may cause false‐positive results. Donations found repeatedly reactive (RR) are discarded regardless of negative HIV‐1/2 nucleic acid testing (NAT) and confirmatory assays results. These donors are notified and deferred if RR in a subsequent donation. We evaluated the introduction of a secondary 4th‐generation serological assay to the overall algorithm performance. METHODS: All donations collected between January 2016 and May 2018 (574, 338) were screened using 3rd‐generation immunoassay (PRISM HIV O Plus) and NAT (Procleix Ultrio/Ultrio Elite). Serology RR donations were tested with 4th‐generation Architect HIV Ag/Ab Combo and Vidas HIV Duo Ultra and a confirmatory assay (Geenius HIV‐1/2). RESULTS: The two 4th‐generation assays found that 86% (179/209 on Architect) and 94% (182/193 on Vidas) of the 3rd‐generation immunoassay RR were negative for HIV‐1/2, which were also negative by confirmatory assay. Only 14% (30/209 on Architect) and 6% (11/193 on Vidas) that were 3rd‐generation HIV‐1/2 RR required confirmation, of which eight donors were confirmed as HIV positive. The probability of missing an HIV‐1 infected donor by this algorithm is one in a million RR cases. CONCLUSION: The introduction of a two‐step serological screening algorithm in blood centers whereby 4th‐generation assay will be performed for all 3rd‐generation RR blood donors will reduce the number of donations requiring confirmation, save time and money, and most importantly, reduce the number of discarded blood donations and allow re‐entry processes.